Solving Economic Dispatch (ED) Problem Using Artificial Immune System, Evolutionary Programming and Particle Swarm Optimization - Nor Rul Hasma, Abdullah; Norazizah, Ghazali; Norshafiqah, Ibrahim; Nadiatul Fatini, Solleh; Rosdiyana, Samad; Mahfuzah, Mustafa; Pebrianti, Dwi (2015)
Nowaday, the demand of the electrical energy is increased due to increment in loading and it is desired to use the existing transmission network to its thermal stability limits. The electrical power system are designed and operated to meet the continuous variation of power demand. The power demand is shared among the generating units and economic of operation is the main consideration in assigning the power to be generated by each generating unit. This paper presents the application Evolutionary Programming (EP), Artificial Immune System (AIS), and Particle Swarm Optimization (PSO) techniques for solving an economic dispatch (ED) problem. The purpose of ED technique in this study mainly to minimize the total generation cost and transmission losses in the system. The proposed optimization technique was validated on 26-bus IEEE Reliability Test System (RTS).